2 kW Modular PEM fuel cell stack for space applications: Development and test for operation under relevant conditions. (15th May 2019) - Giacoppo, Giosuè; Hovland, Scott; Barbera, Orazio
Highlights: An effective design methodology for fuel cell stack design is illustrated. The breadboard configuration influences the cell voltage distribution. The fuel cell stack performances are strongly influenced by the orientation. No appreciable degradation was recorded during cyclic load tests. A high load following capability was noticed. Abstract: A polymer electrolyte fuel cell stack of 2 kW of peak power has been designed, manufactured and tested. Such a fuel cell stack has been envisaged to be applied for manned lunar exploration missions, as secondary energy source for both mobile vehicles and fixed power plants. The stack has been bread-boarded in order to test and demonstrate the technology. The following constraints have been considered during the study: (i) operation with pure hydrogen and oxygen (ii) low humidification levels (iii) use of commercial Membrane Electrode Assemblies. The breadboard has been made consisting of two modules, each of 500 W of nominal power. Specific tests have been conducted to prove the effect of gravity on the breadboard performance and verify its ability to follow variable load profiles over time, representative of different lunar surface exploration missions. The bread-board has shown a good performance during the test campaign, even if some failures of the Membrane Electrode Assemblies have been observed. The study has demonstrated the high performance of the developed stack and the potential of fuel cell technology for use in future human lunar exploration missions. At the same time, it has highlighted serious criticalities related to the reliability and robustness of the commercially available Membrane Electrode Assemblies, which need to be investigated further, before the use of this technology in a real space exploration mission can be possible.